Seasonal Dynamics of Microbial Diversity at a Sandy High Energy Beach Reveal a Resilient Core Community - Degenhardt, Julius; Dlugosch, Leon; Ahrens, Janis; Beck, Melanie; Waska, Hannelore; Engelen, Bert (Frontiers in Marine Science, 2020)
Sandy beaches have received increasing attention due to their global ubiquity and ecological services they provide. Previous investigations on their microbial diversity mostly targeted low energy beaches, lacked seasonality or geochemical information. We now have used a multidisciplinary approach to study the microbial diversity within sediments of a sandy, high energy beach that additionally exhibits submarine groundwater discharge (SGD) in the intertidal. We sampled two transects at three seasons down to a depth of one meter for 16S rRNA gene amplicon sequencing and subsequent correlation of microbial diversity to physico-chemical parameters. We found that advection driven transport of porewater constituents and constant physical reworking of the sediments prevented a distinct formation of vertically stratified redox zones. Consequently, a uniform microbial core community of generalists established independently of sampling site and depth. During spring, the community structure was disturbed by a “subsurface bloom” of Bacteroidetes and Firmicutes, probably due to deeper oxygen and nitrate penetration depths. In summer, the community returned to its equilibrium state with imprints of the subsurface bloom still visible. In our study, we did not detect a clear impact of SGD on microbial diversity, but found an unexpected homogeneous composition and resilience of the microbial community structure.